Grape seed extract reduces oxidative stress and fibrosis in experimental biliary obstruction - DULUNDU, ENDER; ERCAN, FERİHA; ŞENER, GÖKSEL (BLACKWELL PUBLISHING, 2007)
Background and aim: The aim of this study was to assess the protective effect of grape seed extract (GSE) against oxidative liver injury and fibrosis induced by biliary obstruction in rats. Methods: Wistar albino rats were divided into four groups; control (C), GSE-treated, bile duct ligated (BDL), and BDL and GSE-treated (BDL + GSE) groups. GSE was administered at a dose of 50 mg/kg a day orally for 28 days. Serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and lactate dehydrogenase (LDH) levels were determined to assess liver function and tissue damage, respectively. Tumor necrosis factor-alpha (TNF-alpha) and antioxidant capacity (AOC) were assayed in plasma samples. Liver tissues were taken for determination of the hepatic malondialdehyde (MDA) and glutathione (GSH) levels, myeloperoxidase (MPO) activity and collagen content. Production of reactive oxidants was monitored by chemiluminescence (CL) assay. Results: Serum AST, ALT, LDH and plasma TNF-alpha were elevated in the BDL group as compared to the control group and were significantly decreased with GSE treatment. Plasma AOC and hepatic GSH level, depressed by BDL, was elevated back to the control level in the GSE-treated BDL group. Increases in tissue MDA level, MPO activity and collagen content due to BDL were also attenuated by GSE treatment. Furthermore, luminol and lucigenin CL values in the BDL group increased dramatically compared to the control and were reduced by GSE treatment. Discussion: These results suggest that GSE protects the liver from oxidative damage following bile duct ligation in rats. This effect possibly involves the inhibition of neutrophil infiltration and lipid peroxidation; thus, restoration of oxidant and antioxidant status in the tissue.
Keywords: bile duct ligation; grape seed; hepatic fibrosis; lipid peroxidation; rat; PROANTHOCYANIDIN EXTRACT; HEPATIC-FIBROSIS; LIVER FIBROSIS; ANTIOXIDANT ACTIVITY; FREE-RADICALS; IN-VIVO; RATS; ACTIVATION; INJURY; MYELOPEROXIDASE